Economic Policy Statements, Social Media, and Stock Market Uncertainty: an analysis of Donald Trump’s tweets - Perico Ortiz, Hector (Journal of Economics and Finance, 2022)
This paper investigates the impact of economic policy communication via social media on stock market uncertainty. It uses a sample of Donald Trump’s tweets to identify and cluster policy related tweets using a double machine learning approach based on natural language processing. The response of uncertainty to these tweets is then estimated using an event-study design. Tweets about foreign policy and trade, monetary policy, and immigration policy significantly increase market uncertainty as measured by the VIX. Independent of their content, also the frequency of tweets and the intensity of tweet sharing matter for stock market uncertainty. Most of the effects are transitory, reaching their peaks around two hours after the publication of tweets. <
Keywords: Twitter; Donald Trump; Economic Policy Communication; Economic Policy Uncertainty; VIX